2010
DOI: 10.1108/02634501011053586
|View full text |Cite
|
Sign up to set email alerts
|

The importance of destination image analysis to UK rural tourism

Abstract: Purpose -The Forest of Dean attracts relatively low numbers of staying visitors and low visitor spend. The paper aims to explore the image of this destination and identify the potential to visit along with any underlying factors that may deter visitors. Design/methodology/approach -A mix of qualitative and quantitative methods were used to gather and analyse responses to an online survey. Respondents offered a range of words and pictures from which they were asked to select those they felt best represented the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 51 publications
0
44
0
7
Order By: Relevance
“…The smart tourism literature tends to stem from the literature on smart cities, and thus is heavily focussed on urban destinations (Buhalis and Amaranggana, 2014). While urban tourism remains an important area of research focus, rural tourism destinations continue to receive far less attention in the literature (Greaves and Skinner, 2010;Quadri-Felitti and Fiore, 2016). Buhalis (2000) has identified the need for integration of effort amongst a range of service providers in order to create a successful tourist product.…”
Section: Smart Tourismmentioning
confidence: 99%
“…The smart tourism literature tends to stem from the literature on smart cities, and thus is heavily focussed on urban destinations (Buhalis and Amaranggana, 2014). While urban tourism remains an important area of research focus, rural tourism destinations continue to receive far less attention in the literature (Greaves and Skinner, 2010;Quadri-Felitti and Fiore, 2016). Buhalis (2000) has identified the need for integration of effort amongst a range of service providers in order to create a successful tourist product.…”
Section: Smart Tourismmentioning
confidence: 99%
“…Previous studies have shown that in the process of choosing a destination for one's next holiday, one of the factors influencing the decision is the destination image (Gartner, 1994;Baloglu & McCleary, 1999;Chi & Qu, 2008;Greaves & Skinner, 2010). If people promoting a destination understand the development process of a destination image, they can create images appealing to the target audience (Gartner, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Most scientists in the field agree with at least two components of the destination image: the cognitive and affective component (Greaves & Skinner, 2010;Serna, Gerrikagoitia, & Alzua, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations